Replication Data for: Coupling of pollination services and coffee suitability under climate change - Imbach, Pablo; Fung, Emily; Hannah, Lee; Navarro Racines, Carlos Eduardo; Roubik, David W.; Ricketts, Taylor H.; Harvey, Celia A.; Donatti, Camila I.; Läderach, Peter R.D.; Locatelli, Bruno; Roehrdanz, Patrick R. (International Center for Tropical Agriculture, 2017)
CASCADE project “Ecosystem-based Adaptation for smallholder Subsistence and Coffee Farming Communities in Central America”